The Utility of Geographic Information System GIS in Transport Data Integration for Economic Development : Evidence from Ibadan, Nigeria (Global Journal of Human-Social Science, 2012)
This study sets out to assess the capability of Geographic Information System (GIS) in Transport Data Integration for Economic development in Ibadan, Nigeria. The study entails an analysis of transport data need and an assessment of their relevance in economic planning. This need is set against the background of large body of data involved in transportation planning and management. The Methodology entails some processes such as data integration, data standardization and spatial referencing and interfacing. The study shows the importance of referencing of socio-economic data and location referencing in economic planning to assist in economic development. Arc GIS programme is employed for integrating data such as demand data i.e. demographic data, land use data, economic data and travel, supply data such as road networks and related facilities.
Keywords: transport data integration; GIS; economic development